Absence of Thyroid Hormone Induced Delayed Dendritic Arborization in Mouse Primary Hippocampal Neurons Through Insufficient Expression of Brain-Derived Neurotrophic Factor - Yajima, Hiroyuki; Amano, Izuki; Ishii, Sumiyasu; Sadakata, Tetsushi; Miyazaki, Wataru; Takatsuru, Yusuke; Koibuchi, Noriyuki (Frontiers in Endocrinology, 2021)
Thyroid hormone (TH) plays important roles in the developing brain. TH deficiency in early life leads to severe developmental impairment in the hippocampus. However, the mechanisms of TH action in the developing hippocampus are still largely unknown. In this study, we generated 3,5,3’-tri-iodo-l-thyronine (T3)-free neuronal supplement, based on the composition of neuronal supplement 21 (NS21), to examine the effect of TH in the developing hippocampus using primary cultured neurons. Effects of TH on neurons were compared between cultures in this T3-free culture medium (-T3 group) and a medium in which T3 was added (+T3 group). Morphological analysis and RT-qPCR were performed on 7, 10 and 14 days in vitro (DIV). On 10 DIV, a decreased dendrite arborization in -T3 group was observed. Such difference was not observed on 7 and 14 DIV. Brain-derived neurotrophic factor (Bdnf) mRNA levels also decreased significantly in -T3 group on 10 DIV. We then confirmed protein levels of phosphorylated neurotrophic tyrosine kinase type 2 (Ntrk2, TrkB), which is a receptor for BDNF, on 10 DIV by immunocytochemistry and Western blot analysis. Phosphorylated Ntrk2 levels significantly decreased in -T3 group compared to +T3 group on 10 DIV. Considering the role of BDNF on neurodevelopment, we examined its involvement by adding BDNF on 8 and 9 DIV. Addition of 10 ng/mL BDNF recovered the suppressed dendrite arborization induced by T3 deficiency on 10 DIV. We show that the lack of TH induces a developmental delay in primary hippocampal neurons, likely caused through a decreased Bdnf expression. Thus, BDNF may play a role in TH-regulated dendritogenesis.